2003
DOI: 10.1136/adc.88.6.517
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urticaria: association with thyroid autoimmunity

Abstract: Background: Though autoimmune phenomena have been regularly associated with chronic urticaria in adults, data in children are sparse. Aim: To describe our experience with children and adolescents with chronic urticaria and autoimmunity. Methods and Results: Of 187 patients referred for evaluation of chronic urticaria during a 7.5 year period, eight (4.3%), all females aged 7-17 years, had increased levels of antithyroid antibody, either antithyroid peroxidase antibody (n = 4, >75 IU/ml), antithyroglobulin anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 17 publications
(16 reference statements)
3
81
0
1
Order By: Relevance
“…An association between childhood chronic urticaria and thyroid autoimmunity has been postulated [101,104]. It is not clear whether the association is causal, as the majority of children present with hyper-or hypothyroid symptoms either before or some time after the onset of chronic urticaria.…”
Section: Aetiology and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…An association between childhood chronic urticaria and thyroid autoimmunity has been postulated [101,104]. It is not clear whether the association is causal, as the majority of children present with hyper-or hypothyroid symptoms either before or some time after the onset of chronic urticaria.…”
Section: Aetiology and Mechanismsmentioning
confidence: 99%
“…31-47% of children with CU have an autoimmune aetiology with a positive ASST [18,19]. About 4% of children with CU have positive antithyroid antibodies, the majority of these are euthyroid [101] (Table 2).…”
Section: Aetiology and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It shall be mentioned that some studies have not had satisfactory results. For example, in the research by Levy et al no improvement was observed in patients (17). Moreover, in the study by Feibelmann et al no relationship was found (18).…”
Section: Anti-tpo Levels In Patientsmentioning
confidence: 89%
“…Chronic urticaria was observed in 7% to 8% children with autoimmune thyroiditis [13]. In another study, 4.3% of children with chronic urticaria had positive anti-thyroid antibody [14]. If symptoms other than urticaria present, further evaluation must be done.…”
Section: Autoimmunitymentioning
confidence: 99%